Evaluation and Development of a Prescription Service Management Information System in the Pharmacy Installation of Puruk Cahu Hospital - Aryani, Norsarida; Peranginangin, Jason Merari; Rahmawati, Ismi (Jurnal Multidisiplin Madani, 2024)
Information systems have an important role in supporting the health service process, to support the performance of hospital services using computerization. The purpose of this study is to evaluate the prescription service information system with the HOT-FIT (human, organization, technology and net benefit) method at Puruk Cahu Hospital. This study used a cross-sectional quantitative descriptive design  with a sample of 20 respondents. Data collection was carried out by direct observation, interviews with the Head of Pharmaceutical Installation, pharmacists, and pharmaceutical technical personnel, and data analysis by calculating SIM evaluation scores using the SPSS application. The results of the evaluation after development, the human  aspect results are good category with the effectiveness of the application of SIM application after development, the organization  aspect results are good category for the application of management information systems, the technology  aspect obtained good results after development for system implementation. The last aspect of net benefit has good category results. The results of information system development at the pharmaceutical installation of RSUD Puruk Cahu showed a significant increase in human, organizational, technology and net benefit aspects of 5.97; 10.31; 11.88 and 3.00% respectively